Pakej pengaturcaraan linear : LINDO - Masrom, Maslin (Penerbit UTM Press, 1990)
Linear programming is an efficient method for determining an optimal decision, for the problem that involved limited resource. The optimal decision is the one that meets a specified objective of management, subject to various restrictions and constraints. It is normally thought of as a method to be implemented on mainframes. However, this method is already implemented on microcomputers. In recent years, a variety of packages have appeared on the market which is believed capable to solve linear programming problems on recent popular microcomputers. This paper discusses one of the software packages known as LINDO. It touches on what is LINDO, how it is implemented, identifies the commands available and surveys on several advantages, weakness and limitations that occurs in that system.